Three-dimensional nanocomposite formed by hydrophobic multiwalled carbon nanotubes threading titanium dioxide as the counter electrode of enhanced performance dye-sensitized solar cells. Issue 60 (8th June 2016) - Yang, Zhichun; Ahmad, Waqar; Chu, Liang; Al-bahrani, Majid Raissan; Tu, Fanfan; Wang, Yumei; Zhang, Hang; Wang, Xi; Su, Jun; Liu, Nishuang; Li, Luying; Yang, Changping; et al.
Abstract : A novel strategy of fast solvent induced assembly is used to synthesize a three-dimensional (3D) nanocomposite of multiwalled carbon nanotubes (MWCNTs) and TiO2, as the counter electrode (CE) of dye-sensitized solar cells (DSSCs). Abstract : A novel strategy of fast solvent induced assembly is used to synthesize a three-dimensional (3D) nanocomposite of multiwalled carbon nanotubes (MWCNTs) and TiO2, as the counter electrode (CE) of dye-sensitized solar cells (DSSCs). The structure and morphology studies show that the as-prepared nanocomposite possesses a porous structure, large specific surface area and abundant active sites. Electrochemical impedance spectroscopy and cyclic voltammetry analysis reveal that the developed structure facilitates a fast rate of reduction of I3 − and promotes charge transportation. The DSSCs exhibit a remarkable enhanced power conversion efficiency (PCE) of 7.95%, as compared to 7.38% for the conventional Pt CE, after irradiation under standard conditions (AM 1.5G, 100 mW cm −2 ).